Literacy acquisition facilitates inversion effects for faces with full-, low-, and high-spatial frequency: evidence from illiterate and literate adults - Yang, Qi; Zhang, Lina; Chen, Changming; Cao, Xiaohua (Frontiers in Psychology, 2023)
Previous studies have found that literacy acquisition modulates configural face processing (e.g., holistic and second-order configural processing). However, it remains unclear how literacy acquisition impacts another type of configural processing indexed by the face inversion effect, especially with normal or filtered faces. We asked Chinese literates and illiterates to judge whether the second face (or house) picture (experiment 1) /high- (or low-) pass filtered face (experiment 2) was the same as the first one when these stimuli were presented sequentially. Literate adults outperformed illiterate controls in the upright face and house conditions (experiment 1)/ upright high- and low-pass filtered conditions (experiment 2) rather than in the inverted conditions. Notably, the size of the inversion effect (indexed by subtracting inverted accuracy from upright accuracy) was larger in literate than illiterate groups for both experiments. These findings shed light on the fact that literacy acquisition promotes configural face processing.